2020
DOI: 10.1177/0885066620967655
|View full text |Cite
|
Sign up to set email alerts
|

B-Lines Scores Derived From Lung Ultrasound Provide Accurate Prediction of Extravascular Lung Water Index: An Observational Study in Critically Ill Patients

Abstract: Introduction: Visualization of B-lines via lung ultrasound provides a non-invasive estimation of pulmonary hydration. Extravascular lung water index (EVLWI) and pulmonary vascular permeability index (PVPI) assessed by transpulmonary thermodilution (TPTD) represent the most validated parameters of lung water and alveolocapillary permeability, but measurement is invasive and expensive. This study aimed to compare the correlations of B-lines scores from extensive 28-sector and simplified 4-sector chest scan with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
1
22
0
1
Order By: Relevance
“…Mayr et al [24] evaluated the scoring of 28-sector and 4-sector B-Lines US protocols in 50 critically ill patients. They reported significant positive correlation of the 4-sector B-Lines protocol with patient CVP (p = 0.039), EVLW index (p < 0.001), and cardiac index (p = 0.120).…”
Section: Discussionmentioning
confidence: 99%
“…Mayr et al [24] evaluated the scoring of 28-sector and 4-sector B-Lines US protocols in 50 critically ill patients. They reported significant positive correlation of the 4-sector B-Lines protocol with patient CVP (p = 0.039), EVLW index (p < 0.001), and cardiac index (p = 0.120).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we enrolled a heterogeneous population of critically ill surgical patients in which B-lines may not have reflected only pulmonary congestion. While some studies point towards an accurate evaluation of EVLW with the BLS [46], others suggest that the accuracy of EVLW assessment with BLS depends on the studied population [47]. For instance, Seibel et al, in a large heterogeneous population of critically ill patients, found that the correlation coefficient between BLS on LU and EVLW assessed by transpulmonary thermodilution was highly variable, with the highest sensitivity and specificity of BLS to predict EVLW increase being in the subgroup of patients with a PaO 2 /FiO 2 ratio <200 mmHg [47].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography has been demonstrated useful in many studies in the field of cardiology but even more in intensive care or emergency grounds. Perhaps non‐cardiologists have admitted the value of ultrasound more than cardiologists despite the background we have as cardiologists and despite the tricky haemodynamic situation we are frequently facing 14–16 . In the present issue of the Journal, Pellicori et al 17 .…”
Section: Figurementioning
confidence: 94%